A Catechetical Material on the Sacrament of Reconciliation for Volunteer Catechists for the Deaf - De La Cruz, RA, Charmaine (Archīum Ateneo, 2021)
Recognizing the key role of imagination in religious education in the methodology of life integration, this thesis presents a catechetical material to guide volunteer catechists to visually translate the catechesis on the sacrament of Reconciliation for deaf children preparing for their first Confession. This aims for the effective communication of the Christian message by relating God’s unconditional love and mercy with the children’s life experiences. The sacrament of Reconciliation, as an ecclesial visibility of God’s grace, may inspire the deaf children to approach God in the sacrament. The sacrament of Reconciliation may foster transformation of the children’s life experiences, making them confident in the knowledge that they are unconditionally loved, and that they belong to God and the Church. The encounter with Jesus and the Spirit present in the sacrament helps them experience peace and restore their relationship with God and others.